Comparison of methods for the synthesis of silver nanoparticles stabilized in a solid polymethacrylate matrix; Talanta; Vol. 275 - Saranchina N. V. Nadezhda Vasilievna; Bazhenova O. A. Olga Aleksandrovna; Bragina S. K. Sofia Konstantinovna; Semin V. O. Viktor Olegovich; Gavrilenko N. A. Natalia Airatovna; Volgina T. N. Tatiana Nikolaevna; Gavrilenko M. A. Mikhail Alekseevich (2024, 2024)
Title screen